Permainan Simulasi sebagai Teknik Bimbingan Sosial bagi Siswa Sekolah Luar Biasa - Abdul Hadis (Jurnal Ilmu Pendidikan, 2016)
Simulation game as a technique of social guidance in groups may be applied to exceptional students using specific service in accordance with their characteristics and abilities. The purpose of giving simulation is to improve their social adaptation and activities. The simulation is given through role playing and group discussion. By the simulation game, social adaptation and social activities of the exceptional students will be improved